(untitled) (Journal of Interior Design and Academy, 2024)
After the Second World War, the standardization of housing needs led the field of architecture to embrace modular design. This system’s flexibility, where each component is interchangeable, upgradeable, or reconfigurable, allows for easy customization and adaptation to various needs. Modular design offers sustainable solutions for housing centers, ecological villages, and temporary shelters against natural disasters. This study introduces the project "Creating Relocatable/Modular Living Units with Sustainable Building Techniques," part of the TÜBİTAK-2209-A University Students Research Projects Support Program. The project aims to provide relocatable and usable living units globally, focusing on ergonomic, comfortable, and practical usage. Furthermore, the project’s results could be disseminated through journal articles and national/international conference presentations, serving as valuable resources for graduate students’ thesis topics.